Improving Libido and Sperm Quality of Bali Bulls by Supplementation of Moringa oleifera Leaves - N. A. Syarifuddin; A. L. Toleng; D. P. Rahardja; Ismartoyo Ismartoyo; M. Yusuf (Media Peternakan, 2017)
Moringa oleifera (Moringa) leaves contain high levels of nutrition that can be utilized as a feed supplement to increase libido and semen quality. This study was aimed to evaluate the effect of Moringa leaves supplementation on libido and sperm quality of Bali bulls. This study used two-sample t-test on four Bali bulls were kept under individual pens for two periods of eight weeks. During the first period (control), the experimental Bali bulls were fed concentrates (1% of body weight) and rice straw ad libitum. During the second period, the experimental Bali bulls were fed similar to the first period with an additional of Moringa leaves 15% of the weight of the concentrate (treatments). Libido and sperm quality were measured twice a week. Plasma samples were taken three times a day (06:00, 14:00, and 22:00h) on the last day of each period. Plasma testosterone concentrations were analyzed by using ELISA techniques. Variables measured were compared using paired student's t-test. Supplementation of Moringa leaves increased testosterone levels (P<0.05) (4.57 vs 4.79, 0.45 vs 4.78, and 2.35 vs 5.63 ng/mL, respectively during 06.00; 14.00; and 22.00h), increased libido (P<0.05) (7.20±1.49 vs 3.49±0.40 min), and increased both the total motility (P<0.05) (63.99±3.37% vs 84.96±3.09%) and the progressive motility (P<0.05) (52.77±1.76% vs 67.03±3.74%) of sperm. Supplementation of Moringa leaves also increased (P<0.05) the velocity and the amplitude and decreased (P<0.05) the linearity of sperm. It can be concluded that the supplementation of Moringa leaves could increase plasma testosterone concentrations, libido, and sperm motility of Bali bulls.